Pendampingan Revitalisasi Ekstrakurikuler KIR Berbasis Kolaborasi dengan Pendekatan Blended Learning di SMA Negeri 1 Tanggetada - Ernawati, Ernawati; Haris, Iyan Nurdiyan; Kharisma, Gaby Nanda; Hl, Nur Ihsan; Sari, Tri Maniarta; Tendrita, Miswandi; MGB , Fadilah; Muktafia, Muktafia (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2024)
The extracurricular activity of Youth Science Club (Kelompok Ilmiah Remaja/ KIR) will not succeed if it is not managed well by the school. The results of the observation indicate that the interest and potential of students in writing scientific papers are quite significant and highly relevant in supporting the strengthening of the Pancasila student profile. However, the KIR activities have not been well accommodated by the school, which underscores the necessity of conducting this community service activity. The focus and objective of this PKM activity is to provide training and support to partners in revitalizing extracurricular KIR activities so that they can be accommodated intensively using a blended learning approach with various real and virtual media. The results of the Community Service Program (Pengabdian kepada Masyarakat/ PkM) with quantitative descriptive analysis show that the writing skills of the students at the beginning of the mentoring received an average score of 33.15, categorized as very poor, and improved at the end of the mentoring to 63.31, categorized as fairly good. The KIR mentoring teachers also experienced an improvement in their ability to guide students. The results of the descriptive analysis showed that the teachers' understanding at the beginning of the mentoring was an average of 42.22% (categorized as insufficient), and by the end of the mentoring, it increased to 80.67%. (good catageory). Thus, through training and mentoring, they have a better understanding of the appropriate research methodology, effective mentoring techniques, and the use of technology in blended learning. Teachers have the potential to become more effective facilitators in helping students produce quality scientific work. This serves as the foundation for designing the KIR revitalization program with a collaborative and blended learning approach.